Manejo del riesgo en las finanzas del sector de la economía social y solidaria para la industria del chocolate en el cantón Quito - Jami Lema, Nelly Geovanna (2014)
This work aims to research on "Risk Management in Finance Sector for Social and Economic Solidarity Chocolate Industry in the Canton of Quito " the summary of the research is detailed. Deal with the beginnings of the Popular and Solidarity Economy at global and national level where we detail the origin , description, and the experiences of countries that have implemented this type of economy because it has been used as a tool essential in times of crisis, such eradicate poverty. We also indicate agencies which are part of this kind of Economy as regulations and laws that support it. Furthermore, it is presented a short summary of the financial indexes that will be useful in the technical study